Doctrine of sanctification in the theology of Karl Barth - Tribble, Harold W. (The University of Edinburgh, 1937)
The scope of the work in preparation of the present dissertation has been prescribed by the purpose to discover and interpret critically Karl Earth's view of the Christian doctrine of sanctification. The study has centred primarily in his thought. The writer sought first to familiarize himself with the Barthian view as a whole, reading his published works and following his lectures through two summer terms. Then a more detailed study was made of his treatment of sanctification. In Chapter I reference Is made to the chief sources of the material available bearing directly upon his view of this doctrine. The works of Emil Brunner were consulted, particularly with reference to points of difference between him and Barth in respect of sanctification. General theological works, and the creeds and confessions of evangelical Christendom, as well as treatises bearing especially upon this subject, were investigated for the purpose of establishing a background of the development of this doctrine in the history of Christian thought against which Earth's view might be interpreted. But throughout the study the writer's objective has been a critical interpretation of Earth's view in particular rather than a general survey of the doctrine in Christian theology. The development of thought follows the writer's understanding of Earth's view of the doctrine. The task of Interpretation and criticism would have been much simpler if we had a complete statement from him of his interpretation of sanctification, but since that is lacking at present a major part of the task in hand has been to present in brief scope the substance of his view. This fact has given direction to the arrangement of the chapters. In Chapter I an introductory statement is given of the basal conceptions of his entire view, not for the purpose of interpreting his theological position but to set forth the foundation on which his conception of sanctification is to be understood. On the basis of this introductory survey the writer attempted to face the question, To what extent is sanctification in this view a divine, rather than a human, work? The answer took the form of Earth's conception of the objective work of Christ (Chapter 11) and the subjective work of the Holy Spirit (Chapter III) in effecting the sanctification of the believer. The next question was, What solution of the problem of sin does this view offer? And the answer was found in Earth's conception of the relation of sanctification to justification, which is presented in Chapter IV. The doctrine also embraces the problem of sin from the standpoint of the Christian life, after sanctification has occurred. Is the sanctified life one of perfection? What is Christian perfection, and when and where is it to be realized? What are the motives and the objectives of the Christian life that sanctification presents? These questions led to the development of Chapter V. In Chapter VI the question faced is, What is the believer to do in serving God in the present order? The answer is conceived in terms of the Church in God's redemptive purpose. The last chapter presents a summary and conclusion. Is Earth's basal conception of the meaning of sanctification in accordance with the teaching of Scriptures? The conclusion is put in three definitive statements. Is his view sound in relation to Christian ethics? What is his contribution to Christian theology in the statement of this doctrine? The writer has sought the ansv/er to these questions in Earth's doctrine of sanetification rather than in his view as a whole; and he has come to the conclusion that there is something more than a corrective note in the contribution that this view presents. It sets forth a sound basis for a constructive view.
The doctrine of sanctification in the theology of Karl Barth
Keywords: Sanctification; Karl Barth; Theology; Christ; Holy Spirit